Potential and Implementation of Circular Economy in Supporting Continuity Business Culinary at Destinations Tour Religion of Sunan Drajat's Graveyard - Subagiyo, Rokhmat; Syaichoni, Ahmad; Bachtiar, Jusuf; Mashudi, Mashudi; Shoidah, Nadia Nadhirotus (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
The research aims to study the Potential and Implementation of a Circular Economy in Business Culinary in the Tourism Religion of Sunan Drajat's Graveyard Lamongan. Research Methods: The research is field research with a descriptive qualitative approach. Data sources used are primary and secondary data sources, and data collection techniques include interviews. Findings/Results: The study's conclusions disclose a gap between the potency economy big circular with low awareness and the application practice circular among perpetrator business culinary. Conclusion: Some initiative circulars have been done; however, support for adequate policies and incentives from the government is still required. This implication is essential for the development of supportive policies and programs transitioning to economy circular in sector tourism, especially in the region tour religion